2014
DOI: 10.2495/si140151
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the effects of climate change on flood frequency in the Luvuvhu River Catchment, Limpopo Province, South Africa

Abstract: Climate change poses a great risk to natural resources and agriculture in the Luvuvhu River Catchment. The catchment has experienced floods resulting from higher than normal rainfall associated with the Intertropical Convergence Zone and cyclones, which have caused enormous damage to property and impacted negatively on fauna and flora and human livelihoods. In order to understand the dynamics involved in the effects of climate change in the catchment, annual maximum flow data was used to evaluate flood frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…The 1999/00 extremely wet sub-season was also identified by Nkuna and Odiyo (2016) in the LRC. However, findings from research by Kundu et al (2014) indicate that the highest river discharge in the LRC was recorded during 1976/77, which was as a result of an above-average wet season. As shown in Fig.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…The 1999/00 extremely wet sub-season was also identified by Nkuna and Odiyo (2016) in the LRC. However, findings from research by Kundu et al (2014) indicate that the highest river discharge in the LRC was recorded during 1976/77, which was as a result of an above-average wet season. As shown in Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Extremely wet conditions were recorded at a frequency of 2.9 in the first portion of the data and 4.3 in the second portion. Kundu et al (2014) also indicated that the LRC is experiencing a high frequency of extremely wet conditions resulting in floods. However, the late 1980s and most of the 1990s showed no signs of extremely wet conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Determination of magnitude of design floods with a specified exceedance probability is required for design and management of hydraulic structures (bridges, dams) and flood risk management projects. Besides using past flow records to direct projected performance of future flood occurrences, frequency analysis also deploys hydrologic models to generate data to illustrate the estimation of exceedance probability and return periods (Kundu et al, 2014). The longer the period of observed flood peak series, the more realistic the results of the flood frequency analysis because the parameters of the probability distribution functions estimated from longer sample series tend to be close to their population values (Wan Deraman et al, 2017).…”
Section: Flood Frequency Analysismentioning
confidence: 99%
“…Probabilistic model relies on use of existing data to forecast future scenario while deterministic model rely on the different physical parameters to bring out result and verify it with existing data to develop a best fit model (Kundu et al, 2014).…”
Section: Flood Frequency Analysis Probability Distributionsmentioning
confidence: 99%